Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1079/bjn19930090
|View full text |Cite
|
Sign up to set email alerts
|

Effects of galacto-oligosaccharide and bacterial status on mucin distribution in mucosa and on large intestine fermentation in rats

Abstract: The purpose of the present paper was to study the effects of a dietary undigestible carbohydrate and intestinal microflora on mucin distribution (neutral, acid, sulphonated), glycolytic activities: beta-D-galactosidase (EC 3.2.1.23), N-acetyl-beta-D-galactosaminidase (EC 3.2.1.43), N-acetyl-beta-D-glucosaminidase (EC 3.2.1.30), alpha-L-fucosidase (EC 3.2.1.51) and bacterial metabolism (gas production, short-chain fatty acids (SCFA) and lactic acid caecal concentration) in germ-free (GF), conventional (CV) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
20
0
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 27 publications
4
20
0
1
Order By: Relevance
“…All correlation coefficients shown were significant (P < 0·05 constitutes the major part of the mucin in the bulk-phase contents (Meslin et al 1993), from which the inoculum was taken.…”
Section: Carbohydratesmentioning
confidence: 99%
“…All correlation coefficients shown were significant (P < 0·05 constitutes the major part of the mucin in the bulk-phase contents (Meslin et al 1993), from which the inoculum was taken.…”
Section: Carbohydratesmentioning
confidence: 99%
“…A study by Zhong et al (2009) showed that GOS feeding significantly improved intestinal barrier function in rats with severe acute pancreatitis [170] . An earlier study by Meslin et al [88] showed that consumption of β (1–4) GOS [(referred as trans galacto-oligosaccharides (TOS) in the study] modified the mucin cell distribution in the colon of germ-free rats. The authors hypothesized that the lower number of mucus cells observed for the three types of mucins (neutral, acid, and sulphonated) in the proximal colon and the greater number in the distal colon was related to changes in osmolality produced by β (1–4) GOS.…”
Section: Introductionmentioning
confidence: 99%
“…Nos observations en histologie (Meslin et al, 1993) (Bara et al, 1990;Yamori et al, 1989). Perumal et ai (1966) (Filipe, 1979;Mian et al, 1979).…”
Section: Introductionunclassified